Reset Modernity!: Re-Present, Re-Set, Re-Assemble—Bruno Latour |ZKM| Center for Arts and Media Karlsruhe, 16 April–21 August 2016. Issue 1 (2nd January 2017) - Lindner, Peter
Abstract : Reset Modernity! is the latest of three exhibitions organized by Bruno Latour and his team that make use of the expressive potential of artwork to translate his thinking and present it to audiences far beyond academia. It is an extraordinarily ambitious endeavor, permanently oscillating among the three domains of science, arts, and politics, but always firmly rooted in a problematization of any form of representation. No wonder the work of geography, a discipline that has long paid homage to what Latour calls the "devil of Double-Click" (the naive belief in one-to-one representation) by surveying, mapping, and measuring the world, figures prominently here. This review essay elaborates on how Reset Modernity! relates to Latour's latest project, An Inquiry into Modes of Existence (AIME) and uses three pieces of the artwork shown at the exhibition for illustration. Yet in its very form (a text, a scientific journal) it inevitably runs counter to one of the central claims of AIME: that of abandoning the privileged position of scientific texts for the production of truth, breaking science's monopoly on truth speaking, and paving the way for a plurality of veridictions.